ANALISIS KERAGAMAN GENETIK KEDELAI INTRODUKSI MENGGUNAKAN MARKA MIKROSATELIT - Nugroho, Kristianto; Terryana, Rerenstradika Tizar; Reflinur, nFN; Asadi, nFN; Lestari, Puji (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2017)
Soybean (Glycine max (L.) Meriil) is an important crop next to rice and corn. The development of improved varietyare important to increase national soybean production. The introduced soybean varieties is one of genetic resourcesthat can be used to create improved soybean varieties. The aim of this study was to analyze 35 introduced soybeancultivars using 15 microsatellite markers. The research was conducted in ICABIOGRAD Molecular Biology Laboratory,in January-March 2016. PCR analysis was scored as binary data and the collected data was analyzed using NTSYS andPowerMarker. Specific morphological characters from each soybean cultivar determine the genetic diversity. Significantpositive correlations were identified among morphological characters which would be helpful to improve the desiredcharacter. The result showed that 189 alleles were detected with average of 12.6 alleles per marker. The polymorphismlevel (PIC) was 0.86 (0.76-0.95). There were 12 of total markers having PIC>0.80 indicating their robustness todiscriminating soybean cultivars. The average major allele frequency was 21% and ranges from 8% (Satt100) to 39%(Satt125). Five SSRs were able to distinguish heterozygosity which varied from 0.41 (SoyF3H) to 0.82 (Satt333). Thephylogenetic analyses showed that the 35 introduced soybean cultivars were grouped into two clusters (coefficient ofsimilarity 0.82) consisting of 13 and 22 cultivars according to each genetic background without considering its countryorigin. Both the microsatellite markers and genetic diversity information in this study could be useful to assist crossingstrategy with utilizing introduced genetic materials in future soybean breeding in Indonesia.